Promotion of Literacy in Sub-Saharan Africa: Goals and Prospects of CAPOLSA at the University of Zambia - Serpell, Robert (Human Technology, 2014)
The convergence of two complementary agendas motivated collaboration between two universities (in Zambia and Finland) to establish the Centre for the Promotion of Literacy in Sub-Saharan Africa (CAPOLSA), focused on initial literacy learning in indigenous languages. The project's mandate and activities are closely related to Zambia's national context of literacy and educational provision, emerging trends in information and communication technology, and the University of Zambia's institutional context of research and development on literacy, child development, and education. CAPOLSA has afforded opportunities for enhancing the working relations between the national university and government and for contributing to the development of institutional linkages and consultative forums. Collaboration between various disciplines, institutions, and economic sectors characterizes CAPOLSA's activities. Important areas of progress envisaged include institutional development, growth of a sustainable community of researchers whose collective efforts will increase the scale of Africa's contribution to international knowledge, and evidence-based planning at the interface between humans and technology.